Guiding Principles For Islamic Labor Code And Business Ethics - Mohamad Zaharuddin Zakaria; Nisar Mohammad Ahmad; Ahmad Zaki Salleh; Mushaddad Hasbullah; Abdulsoma Thoarlim (HRMARS, 2024)
Non-Indexed Publication